Strategic Pluralism and Monism in Heterodox Economics. (June 2018) - Jackson, William A.
Pluralism is frequently supported by heterodox economists, but their rationale for it is not always transparent. It could be advocated for strategic reasons, as a response to the institutional power of orthodoxy, or for fundamental reasons, as a program for how economics should best be done. This paper evaluates strategic pluralism, compares it with the alternative of strategic monism, and relates both strategies to long-term objectives.